Current Issues of Higher Education Pedagogy and University Teachers' Skills Development - N. D. Lyssakov; E. N. Lyssakova (Moscow Polytechnic University, 2021)
The article addresses the current issues of pedagogy of higher education that should be presented in skills development programs in consideration of aerospace education specifics. According to the contemporary Russian and foreign researches, current issues of pedagogy are concentrated in such areas as the development of education in connection with the formation of learning and teaching processes. It is feasible to discuss systematically these  problems in teacher training and professional development courses and formulate scientific and practical recommendations.The article dwells on the three research areas in pedagogy of higher education: 1) features of the modern educational process; 2) student as a subject of educational activities; 3) university teacher as a subject of pedagogical activities. A student as a subject of learning is characterized not only by criteria of his cognitive and motivational development, but also in the context of mental health risks in the conditions of challenges and threats of the digital world. The analysis of modern student's value orientations is an important aspect of higher education pedagogy in order to influence teaching and educational processes.A teacher as a subject of pedagogical activity is studied from the standpoint of his professional success. Such factors of his professionalization as motivation, pedagogical communication, stress resistance in various working conditions are considered.